DOES WORKING CAPITAL MANAGEMENT ABLE TO INCREASE SUSTAINABLE GROWTH THROUGH ASSET UTILIZATION? - Nastiti, Pambayun Kinasih Yekti; Atahau, Apriani Dorkas Rambu; Supramono, Supramono (The European Journal of Applied Economics, 2020)
Working capital management has a strategic role to maintain a balance between liquidity and profitability so that firms have greater opportunities to operate sustainably. This study mainly aims to investigate the ability of working capital management increase sustainable growth through asset utilization. We run panel data regression on manufacturing firms listed in the Indonesian Stock Exchange for the years of 2010-2017 as our sample. By controlling for leverage, sales growth, and firm size, our empirical results demonstrate that working capital management negatively affects firms’ asset utilization. Further, the study also finds that asset utilization positively affects sustainable growth. Eventually, we empirically show that asset utilization mediates the relationship between working capital management and sustainable growth. The findings imply that if Indonesian manufacturing firms manage to have efficient working capital management, they are more likely to utilize their assets efficiently that in turn will increase their growth optimally without causing problems to their cash.
Keywords: working capital management, asset utilization, sustainability growth, cash conversion cycle